Study of effects of Sudarshan Kriya on Postmenopausal symptoms among central India women population : A preliminary study - Patil, Rajeshree Tukaram; Patil, Renuka Vivekanand; Ughade, Suresh Narayanrao; Hatwar, Manjusha Sureshchandra (Asian Journal of Medical Sciences, 2017)
Background: Menopausal health concerns mainly include the vasomotor symptoms, cardiovascular symptoms, osteoporosis, cancer, sexual problems and urogenital atrophy. Our life style today leads to a lot of stress, depression and anxiety. Prolonged stress can make one experience the symptoms like menopause (though not actually inducing it). Yoga exercise meditation and life style modification have relieved stress and enhanced the quality of life. Sudarshan Kriya (SK) is a rhythmic breathing technique with 4 breath components. It has varied effects on body especially acting by relief of stress. Aims and Objective: Assess the effects of SK on the commonly perceived symptoms experienced by the postmenopausal women in central India. Materials and Methods: A random sample of 156 women was interviewed by administering a pre-designed and pre-tested questionnaire. Questionnaire included 14 frequently occurring symptoms. Stress was scored on Likerts scale to assess the severity. (Score total =lowest 0 and highest 42). Those women doing regular SK for at least more than 1 year before the final menstrual period (n= 79) formed the Study group and women doing SK for less than 1year, women following other health practices, or not following any health practice at all (n=77) belonged to the Control group. Results: Women doing SK were found to be happier and content as compared to controls. SK with vegetarian diet was found effective in lowering the scores. Combining SK with exercises and yoga together can reduce the score to the lowest level. Minimum two years of regular practice was found enough to yield low scores and best quality of menopausal transformation. Conclusion: Initiating SK into the lives of postmenopausal women at the right time can assure a less morbid, more comfortable and a better quality of postmenopausal life. Asian Journal of Medical Sciences Vol.8(5) 2017 58-63